Are informal family caregivers stigmatized differently based on their gender or employment status?: a German study on public stigma towards informal long-term caregivers of older individuals - Larissa Zwar; Matthias C. Angermeyer; Herbert Matschinger; Steffi G. Riedel-Heller; Hans-Helmut König; André Hajek (BMC, 2021)
Abstract Background Stigma and informal caregiving are determinants for health and wellbeing, but few studies have examined stigma towards informal caregiving. Public stigma may be expressed differently towards caregivers depending on their gender and employment status due to societal norms. Therefore, this study analyzes if there is a difference in public stigma shown by the general population toward informal caregivers of care recipients aged 65 years or older based on the observed caregiver's gender or working status. Methods A cross-sectional study was conducted in Germany. Data from 1038 adult participants from the general population in Germany were assessed with an Online-Survey. They were recruited with a quota-system based on the German micro census. Participants were randomly assigned to one of 16 vignettes describing a caregiving situation, which varied in the caregiver's gender and working status, and care recipient's gender and type of impairment. After reading the vignette, they were asked to provide sociodemographic information and complete three questionnaires on public stigma assessing their emotional (Emotional Reactions), behavioral (Social Distance) and cognitive reaction (Statements on informal caregivers) to the caregiver described in the vignette. Regression analyses, adjusted for sociodemographic data of the participants, were conducted. Results Findings indicated an association between reading about male caregivers and increased social distance, compared with reading about female caregivers. Reading about working caregivers was associated with decreased social distance and increased appreciative statements, compared to reading about non-working caregivers. Analyses after stratifying by gender of the caregiver in the vignette indicated an association between reading about female working caregivers and increased appreciative statements, compared to reading about female non-working caregivers. When stratifying by working status, an association was found between reading about male working caregivers and increased social distance, when compared to reading about female working caregivers. Conclusions This study's findings indicate that gender and working status of the perceived informal caregivers are of relevance to the public stigma directed towards these caregivers. Male and non-working informal caregivers were shown more public stigma than female and working informal caregivers. Thus, interventions to reduce public stigma, in particular towards male and non-working caregivers, are recommended.